2021
DOI: 10.1159/000519413
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal <b><i>Helicobacter pylori</i></b> Treatment for the Present and the Future

Abstract: <b><i>Background:</i></b> <i>Helicobacter pylori</i> eradication treatments are widely performed to improve gastric mucosal inflammation, promote ulcer healing, and reduce the incidence of gastric cancer. However, there are several issues associated with <i>H. pylori</i> eradication treatment. First, various treatment regimens are currently used worldwide, and the standard treatment varies with region and country. Second, the antimicrobial resistance of <i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
0
24
0
4
Order By: Relevance
“…The use of clarithromycin can drive antibiotic resistance at the population level [53] and would not be effective for the treatment of clarithromycin-resistant infections [54]. Therefore, Suzuki et al suggested the use of vonoprazan dual therapy because it may provide comparable eradication rates, improve safety and tolerability, and minimize antimicrobial resistance [55]. Moreover, ACG guidelines recommend avoiding clarithromycin in locations where the resistance rate to clarithromycin is greater than 15% [9].…”
Section: Discussionmentioning
confidence: 99%
“…The use of clarithromycin can drive antibiotic resistance at the population level [53] and would not be effective for the treatment of clarithromycin-resistant infections [54]. Therefore, Suzuki et al suggested the use of vonoprazan dual therapy because it may provide comparable eradication rates, improve safety and tolerability, and minimize antimicrobial resistance [55]. Moreover, ACG guidelines recommend avoiding clarithromycin in locations where the resistance rate to clarithromycin is greater than 15% [9].…”
Section: Discussionmentioning
confidence: 99%
“… 20 There is evidence that timely diagnosis and eradication of H. pylori can improve gastric mucosal inflammation, promote ulcer healing, and reduce the incidence of gastric cancer. 21 The virulence of the strain plays an important role in the clinical consequences of a H. pylori infection. 22 H. pylori has two important toxins, cagA and vacA , which are the main pathogenic factors of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase is a marker of neutrophil infiltration during inflammation. There is one clinical study, shown that oral herbal compounds for 1 mo can remarkably increase mucosal Mucin5AC (MUC5AC) (human mucin gene) levels in gastric ulcer patients [17] .…”
Section: Groupmentioning
confidence: 99%